Pengajaran Bahasa Arab Dengan Metode Eklektik - Anwar Abd. Rahman (Jurnal Adabiyah: Humanities and Islamic Studies, 2011)
Arabic teaching consist of teaching and learning method and anything related to all aspect of teaching such as, material, objectives, methods and evaluation. Eclectic method is a method used to teach by combining some methods which are considered better to make better class.  Teaching arabic looks more difficult than teaching another languages, it is due to the arabic pattern is  more variative and has more meaning.